2020
DOI: 10.1167/tvst.9.9.5
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and Choroidal Vasculature in Patients with Marfan Syndrome

Abstract: To assess the retinal and choroidal vasculature in patients with genetically confirmed Marfan syndrome (MfS). Methods: This prospective, case-control, observational study included 48 eyes of 24 patients with a genetic diagnosis of MfS and compared them with 52 eyes of 26 healthy controls. Best-corrected visual acuity, choroidal and retinal thickness measured by spectral domain-optical coherence tomography, retinal and choroidal vasculature characterized by optical coherence tomography angiography, were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In a previous case report, an MFS patient with an FBN1 mutation developed an aneurysm and was detected with abnormal retinal vascular morphology in both eyes [ 51 ]. Another study investigated the retinal vasculature alterations in genetically confirmed MFS and found that the severity of MFS was significantly correlated with impairments in the retinal vasculature [ 52 ]. Consistent with these findings, in our study, we observed that (1) the genes with clear biological effects on connective tissue disorders like MFS were also associated with oculomics of RVFs (Supplementary Figure 2 ); (2) the identified oculomics of RVFs had a capability in predicting systemic aneurysm, which was more precise than baseline information.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous case report, an MFS patient with an FBN1 mutation developed an aneurysm and was detected with abnormal retinal vascular morphology in both eyes [ 51 ]. Another study investigated the retinal vasculature alterations in genetically confirmed MFS and found that the severity of MFS was significantly correlated with impairments in the retinal vasculature [ 52 ]. Consistent with these findings, in our study, we observed that (1) the genes with clear biological effects on connective tissue disorders like MFS were also associated with oculomics of RVFs (Supplementary Figure 2 ); (2) the identified oculomics of RVFs had a capability in predicting systemic aneurysm, which was more precise than baseline information.…”
Section: Discussionmentioning
confidence: 99%
“…Other fibrillin-1-interacting proteins may be involved in angiogenesis as well. While many pathological aspects in individuals with MFS are known for decades, retinal vascular pathophysiology was only described recently ( 9 , 10 ). These studies show decreased retinal capillary vessel density in patients with MFS, correlating with aortic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, defective fibrillin-1-rich ciliary zonules cause ocular lens dislocation ( 8 ). However, individuals with MFS also present a reduction in the density of capillaries in the retina, whose etiology is entirely unknown ( 9 , 10 ).…”
mentioning
confidence: 99%
“…Poor image quality according to specific criteria including low-quality index (<7), presence of blink artifacts, motion or doubling artifacts caused by poor fixation, and media opacities obscuring the view of the vasculature were considered exclusion criteria. All examinations were performed by the same expert ophthalmologist [30,32,39,40]. All OCT-A measurements were performed at the same time of the day (specifically, 3:00-5:00 p.m.) in both patients and controls [30].…”
Section: Ophthalmological Assessmentmentioning
confidence: 99%